Mass‐mortality in green striped tree dragons (Japalura splendida) associated with multiple viral infections. (14th September 2013) - Behncke, H.; Stöhr, A. C.; Heckers, K. O.; Ball, I.; Marschang, R. E.
Abstract : In spring 2011, high mortality in association with skin lesions, systemic haemorrhages and necrosis occurred in a group of green striped tree dragons ( Japalura splendida ) which were imported from southwestern China via Florida to Germany. Infections with various endoparasites were diagnosed in coprological examinations. Different antiparasitic and antibiotic treatments over a period of three months did not reduce the mortality rate. The remaining animals were therefore euthanased and submitted for additional testing. Predominant findings in pathological examination were granulomatous and necrotising inflammation of the skin, vacuolar tubulonephrosis of the distal renal tubules, hyperaemia and liver necrosis. Eosinophilic intranuclear and basophilic intracytoplasmic inclusion bodies were detected in the liver. Virological testing (PCR and virus isolation methods) demonstrated the presence of ranavirus, adenovirus and invertebrate iridovirus.